2020
DOI: 10.1017/s0007114520000574
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterolaemia associated with parenteral nutrition administration in adult patients

Abstract: Vegetable lipid emulsions (LE) contain non-declared phytosterols (PS). We aimed to determine PS content depending on the brand and LE batch, and in adult hospitalised patients treated with parenteral nutrition (PN), to establish the association between plasma and administered PS. Part I was the LE study: totals and fractions of PS in three to four non-consecutive batches from six LE were analysed. Part II was the patient study: patients with at least 7 previous days of PN with 0·8 g/kg per d of an olive/soyabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, it mainly has side effects such as elevated transaminases and myopathy, including myalgia, myositis, Oxidative Medicine and Cellular Longevity and transverse muscle melting, which predispose to poor prognosis [6,28]. PS are widely used in medical research because of their widespread presence in nature and their powerful properties [29]. Multiple studies have shown that PS significantly reduce blood cholesterol concentrations which has important clinical value in the management of obesity, HLP, and diabetes [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…However, it mainly has side effects such as elevated transaminases and myopathy, including myalgia, myositis, Oxidative Medicine and Cellular Longevity and transverse muscle melting, which predispose to poor prognosis [6,28]. PS are widely used in medical research because of their widespread presence in nature and their powerful properties [29]. Multiple studies have shown that PS significantly reduce blood cholesterol concentrations which has important clinical value in the management of obesity, HLP, and diabetes [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of high doses of intravenous lipids, that are high in n-6 PUFAs and phytosterols (like the ones based on soybean oils), can contribute to the development of parenteral nutrition-associated liver disease [23]. ILEs based exclusively on fish oil reduce plasmatic phytosterol levels and are associated with an improvement in liver profile [24,25]. In our study, regarding analytical data, we did not find any differences in liver profile, neither in the percentage of patients with an increase in liver enzymes nor in the number of patients with liver complications.…”
Section: Lipid Control and Liver Enzymesmentioning
confidence: 99%